Pendampingan Penggunaan Mobile Banking dan QRIS untuk Peningkatan Transaksi UMKM - Hutabarat, Arnold Sultantio; Effendy, Marwan; Setiawan, Jonathan Marcellinus (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
The development of digital payment systems has encouraged Micro, Small, and Medium Enterprises (MSMEs) to adapt by using mobile banking and the Quick Response Code Indonesian Standard (QRIS) as cashless transaction methods. However, in practice, many MSMEs have not yet optimally utilized these technologies due to low levels of digital financial literacy, limited technical skills, and concerns about transaction security. This Community Service program aims to enhance MSMEs’ digital financial literacy, improve their ability to use mobile banking and QRIS, and increase both the volume and value of non-cash transactions among MSMEs. The program was implemented using a participatory education approach, hands-on training, and continuous mentoring. The activities were carried out through several stages, including preparation, training implementation, mentoring, and evaluation. Data were collected through observations, interviews, pre- and post-training questionnaires, and activity documentation. Data analysis was conducted using descriptive quantitative and qualitative methods to capture changes in MSMEs’ understanding and transaction behavior. The results indicate an improvement in MSMEs’ understanding of the concepts and benefits of digital payments, an increase in the number of MSMEs that own and actively use QRIS, and a rise in non-cash transactions after the mentoring activities. MSME participants also demonstrated more positive attitudes and greater confidence in using mobile banking and QRIS in their daily business operations. These findings show that practical and contextual mentoring is effective in promoting the adoption of digital payment systems among MSMEs. This program makes a tangible contribution to supporting digital financial inclusion and strengthening MSME performance. The mentoring model applied is simple and flexible, making it potentially replicable for other MSMEs with similar characteristics and challenges. Keywords: MSMEs, mobile banking, QRIS, digital financial literacy, community service